2018
DOI: 10.1016/j.jaci.2018.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism for initiation of food allergy: Dependence on skin barrier mutations and environmental allergen costimulation

Abstract: These studies uncover mechanisms for food allergy sensitization and anaphylaxis in neonatal mice that are consistent with features of human early-life exposures and genetics in patients with clinical food allergy and demonstrate that changes in barrier function drive development of anaphylaxis to food allergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 95 publications
5
92
1
1
Order By: Relevance
“…78 In contrast, Walker et al showed that, in filaggrin (FLG)-deficient mice, epicutaneous sensitization to peanut or OVA required costimulation with Alternaria alternata or house dust mite extract. 97…”
Section: E Xperimental Model S Of Epi Cutaneous S En S Itiz Ati Onmentioning
confidence: 99%
“…78 In contrast, Walker et al showed that, in filaggrin (FLG)-deficient mice, epicutaneous sensitization to peanut or OVA required costimulation with Alternaria alternata or house dust mite extract. 97…”
Section: E Xperimental Model S Of Epi Cutaneous S En S Itiz Ati Onmentioning
confidence: 99%
“…Luminal food antigens are taken up by intestinal dendritic cells, directly or through the mediation of macrophages, and presented to naïve CD4 + T cells in draining lymph nodes . TGFβ‐ and retinoic acid‐producing dendritic cells favor the production of antigen‐specific, forkhead box protein 3 + (FoxP3 + ) regulatory T cells (T reg ) that play a pivotal role in gut immune tolerance, mainly through the production of IL‐10 and TGFβ …”
Section: Putative Mechanisms Of Actionmentioning
confidence: 99%
“…38 TGFβ-and retinoic acid-producing dendritic cells favor the production of antigen-specific, forkhead box protein 3 + (FoxP3 + ) regulatory T cells (T reg ) that play a pivotal role in gut immune tolerance, mainly through the production of IL-10 and TGFβ. 39 Regarding the mechanisms of FA induction, the exposure to food allergens through a damaged skin barrier may cause allergic sensitization. 39,40 Epithelial disruption in the gastrointestinal tract may interfere with the above-mentioned tolerance pathways and induce the release of damage-driven cytokines, such as IL-25, IL-33, and thymic stromal lymphopoietin (TSLP), thus favoring a skewing to Th2 immune response.…”
Section: Putative Mechanis Ms Of Ac Ti Onmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, the vast cultural diversity, food avail-ability, tropical and subtropical climates, as well as peanut intake tendencies, all lead to differing dietary and food preparation habits that may not be found in developed economies, all of which cause variability among peanut allergy development. 7,8 In Mexico, the issue regarding peanut allergy among adults has seldom been analyzed; there is a generally held notion that food allergy is more of a problem within the pediatric population. Given these circumstances, the objectives of our study were: Firstly, to determine the prevalence of peanut allergy among a sample group with allergic respiratory diseases, and secondly, to describe the symptoms that are most frequently triggered by peanut ingestion among our sample group of patients.…”
Section: Introductionmentioning
confidence: 99%